Substitusi Tepung Ikan Dengan Tepung Maggot Black Soldier Fly (Hermetia illucens) Terhadap Penampilan Burung Puyuh (Coturnix coturnix japonica) - Rahmadani Ansyari; Achmad Jaelani; Neni Widaningsih (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2012)
The Study substitute Fish Meal with Maggot Meal Black Soldier Fly (Hermetia illucens) Appearance Against Quail (Coturnix coturnix japonica) was carried out at 36 Jalan Palasari Waas RT. 1 RW. 4 Rural District Sukasari Pameungpeuk Bandung regency, West Java, which runs from January to February 2012. The research aims to  determine the substitution of fish meal with maggot meal Black Soldier Fly (Hermetia illucens) the appearance of the female quail in the growth phase. The design used in this study is completely randomized design (CRD) with four replications per treatment 5 replicates consisted of 10 female quails so that the whole 200 tail. As for treatment, namely R1 (16.00% + 0% fish meal flour maggot), R2 (12.00% + 6.47% fish meal flour maggot), R3 (8.00% + 12.94% fish meal flour maggot ), R4 (4.00% + 19.41% fish meal flour maggot), and R5 (0% fish meal flour maggot + 25.88%), with an average initial body weight of 48.01 grams / tail-old 3 weeks. The results showed that the substitution of fish meal with maggot meal significantly (P <0.05) in female quail consumption. While the weight gain, feed conversion and weight gain end female quail had no significant effect (P <0,05).